Chip Scale Package, CSP : Design, Materials, Processes, and Aplications - Lau, John H. (McGraw-Hill)
Contents: Flip chip and wire bond for CSP; Customized leadframe based CSPs; CSP with flexible substate; CSP with rigid substrate; Wafer-level redistribution CSPs.